Ø¨Ø¹Ø¶ Ø§Ù„Ù…Ø±ØªÙƒØ²Ø§Øª ÙˆØ§Ù„Ø£Ø³Ø§Ø³ÙŠØ§Øª ÙÙŠ ØªÙ‚Ø¯ÙŠÙ… Ø§Ù„Ù‚ÙˆØ§Ø¹Ø¯ Ù„Ù„Ù†Ø§Ø·Ù‚ÙŠÙ† Ø¨ØºÙŠØ± Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© - Hilali, Sana; Alaoui, Mohamed Ismaili (Universitas Ahmad Dahlan)
Applied linguistic scholars agree that grammar is an essential aspect of teaching Arabic to a non-native speaker. Therefore, it is impossible to conduct any language to students without teaching its grammar, and it is challenging for the teachers. This research focuses on the overview of Arabic grammatical and its importance in teaching Arabic to non-native speakers. Additionally, it describes what aspects teachers should pay attention to in teaching grammar and offers several methods to be implemented based on academic research and teaching experience.Â